Comparative Analysis of Lung Ultrasonography and Chest Radiography in Suspected Cases of Pneumonia in Critically Ill Patients - Ashvin Pansuriya (Asian Journal of Medical Radiological Research, 2021)
Background: The present study compared lung ultrasound (USG) and chest radiography in alleged cases of pneumonia in seriously ill patients. Subjects and Methods: A total of 70 subjects attending to the emergency room with symptoms of pneumonia and those were admitted in ICU with a suspicion of pneumonia over an eighteen month period were included in this study. Patients then underwent imaging studies in the form of chest radiograph and lung ultrasound. Results: Out of 70 subjects, males were 39 and females were 31. Age group 20-30 years had 4 patients, 30-40 years had 6, 40-50years had 10, 50-60 years had 16 and >60 years had 20 subjects. The dissimilarity was significant (P< 0.05). Chest x ray reveled 50 out of 70 cases positive and 20 negative and USH showed 65 positive and 5 negative. Positive predictive value (PPV) of chest x- ray was 71.4% and USG was 92.8%. Conclusion: Authors found that lung ultrasound is an effective radiological implement for the assessment of suspected cases of pneumonia as compared to chest x ray.